The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5388/aon.2014.14.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High Dose Methotrexate Administration Between the Inpatient and Outpatient Setting in Children with Acute Lymphoblastic Leukemia

Abstract: 연구의 필요성2010년) administration in either the inpatient (N = 70) or outpatient setting (N = 70) from January to July 2012 were included. In the outpatient setting, HD-MTX was administered intravenously (IV) over 6 hours and included hydration with sodium bicarbonate (2000 ml/m 2 / for 12 hours). Daily visits to the outpatient setting followed. Leucovorin was given 24 hours after MTX at a standard dose (15 mg/m 2 IV bolus) every 6 hours. We compared the serum drug levels of MTX, hematologic and renal toxicity, hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Current evidence is informative on the safety of ambulatory supportive care for HD MTX and its financial benefits. The transition to ambulatory care for HD MTX and supportive care is safe and effective (Choi et al, 2014;Holdsworth et al, 1997;Lange et al, 1988;Lashlee & O'Hanlon Curry, 2007;Lippert et al, 2017;Mahadeo et al, 2010;Newton & Ingram, 2014;Sive et al, 2012;Zelcer et al, 2008). Mahadeo et al (2010) identified that of the 97 ambulatory HD MTX administrations 99% were successfully completed outpatient; zero had elevated MTX levels at 24 hours, 26% experienced typical neutropenia, 4% experienced thrombocytopenia, and 1% experienced leukopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence is informative on the safety of ambulatory supportive care for HD MTX and its financial benefits. The transition to ambulatory care for HD MTX and supportive care is safe and effective (Choi et al, 2014;Holdsworth et al, 1997;Lange et al, 1988;Lashlee & O'Hanlon Curry, 2007;Lippert et al, 2017;Mahadeo et al, 2010;Newton & Ingram, 2014;Sive et al, 2012;Zelcer et al, 2008). Mahadeo et al (2010) identified that of the 97 ambulatory HD MTX administrations 99% were successfully completed outpatient; zero had elevated MTX levels at 24 hours, 26% experienced typical neutropenia, 4% experienced thrombocytopenia, and 1% experienced leukopenia.…”
Section: Introductionmentioning
confidence: 99%
“…( 42 ) In extreme situations and with close monitoring, administration of high dose methotrexate on outpatient basis has also been found safe. ( 43 ) An individualized decision to continue subsequent cyclophosphamide, cytarabine or etoposide on outpatient basis can be made if patients are expected to comply with instructions on neutropenic care and regular follow up. ( 44 ) As ALL is curable disease in many age groups, it is recommended that priority be given to minimizing treatment delays.…”
Section: Introductionmentioning
confidence: 99%
“…8 This outpatient protocol presents the results of a quality improvement project conducted to analyze the methods used in our hospital to provide urinary alkalinization and hematological rescue to patients with NHL undergoing treatment with HDMTX. 11,12 In this study, the aim is to analyze the feasibility of an oral alkalinization and leucovorin rescue regimen that ensures the safety of outpatient treatment with HDMTX for CNS prophylaxis in NHL patients.…”
Section: Introductionmentioning
confidence: 99%